Characteristics of Groundwater Hydrochemistry and Stable Isotopes (δ18O & δ2H) in Cadasari, Banten, Indonesia - Hidayat, Hadi; Yoseph, Boy; Muda Iskandarsyah, Teuku Yan Waliana (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
Groundwater is an essential resource for drinking and domestic use, displaying significant diversity in volcanic regions.This study focuses on Cadasari, Banten, Indonesia, and aims to determine the hydrochemical characteristics of groundwater and the stable isotopes (δ18O & δ2H). Hydrogeological mapping was employed, and analytical data were collected from 20 groundwater sources, including springs, rivers, and wells, at elevations ranging from 167 to 928 meters above sea level. The hydrochemical analysis revealed various groundwater types, such as Ca-HCO3, Ca+Mg-HCO3, Na+K+Ca-HCO3, and Na+K+Ca-Cl. These variations in groundwater types are attributed to differences in volcanic lithofacies. Gibbs and Gaillardet’s diagrams indicate that water-rock interaction processes primarily influence the variability of these groundwater facies in Cadasari, highlighting the significant role of silicate minerals in the groundwater's geochemistry. The isotopic composition of borehole samples shows an average isotope ratio of -7.0 ‰ for δ18O and -41.7 ‰ for δ2H, while dug well samples have average ratios of -6.1 ‰ for δ18O and -34.9 ‰ for δ2H. Spring samples exhibit an average isotope ratio of -6.7 ‰ for δ18O and -39.3 ‰ for δ2H. The isotopic composition across the groundwater samples suggests that the water in this area is of meteoric origin.